2020
DOI: 10.2166/h2oj.2020.054
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and biochemical oxygen demand change in a typical Midwest stream in the past two decades

Abstract: Nitrate and organic contamination from Midwest rivers, including the White River at Muncie, IN, has been an on-going concern and contributes to the hypoxic zone in the Gulf. Despite rich data, recent water quality changes have rarely been investigated. This study employed 16 years of continuous monitoring data, including biochemical oxygen demand (BOD), dissolved oxygen (DO), and nitrate–nitrite as nitrogen (NN) from five sites near Muncie, and analyzed the water quality trend and pollution sources. A novel ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The conformity denotes little influence from anthropogenic activities in the study area. High nitrate is known to increase the growth of plants and algae in the water body and this contributes to high BOD and the depletion of oxygen (Poulsen et al, 2018;Alam et al, 2021). The low nitrate values recorded in this study corresponds with the low BOD observed.…”
Section: Discussionsupporting
confidence: 74%
“…The conformity denotes little influence from anthropogenic activities in the study area. High nitrate is known to increase the growth of plants and algae in the water body and this contributes to high BOD and the depletion of oxygen (Poulsen et al, 2018;Alam et al, 2021). The low nitrate values recorded in this study corresponds with the low BOD observed.…”
Section: Discussionsupporting
confidence: 74%
“…Microbes use dissolved oxygen to decompose the organic matter in a water sample. The amount of oxygen used is directly related to the amount of organic matter present, as assessed by the BOD test (Alam et al, 2021). If persistently high BOD and low DO values are allowed, it can disrupt the stability of aquatic biota, ultimately leading to their demise.…”
Section: Parameters Of Chemicalmentioning
confidence: 99%
“…Ravansalar & Rajaee (2015) obtained an R 2 value of 0.949 using wavelet-based ANNs against a value of 0.381 using ANNs in the prediction of electrical conductivity for Asi River, Turkey. Alam et al (2021) have used Weighted Regression on Time, Discharge and Seasons (WRTDS) to analyze the long-term trends of water quality especially that of BOD, DO, and nitrate-nitrite (NN), and found the influences of wastewater treatment plants (WWTPs), combined sewage outflows (CSOs), and agricultural runoff in increase of pollution levels for White River at Muncie, IN, USA. However, the current study is limited to the temporal prediction of WQPs from climate and land use parameters and has not considered the influences of discharge and seasons separately.…”
Section: Matlab Simulations Using the Levenberg-marquardt Algorithm R...mentioning
confidence: 99%